Embedded infrared fiber-optic sensor for thermometry in a high temperature/pressure environment - Yoo, Wook Jae; Jang, Kyoung Won; Moon, Jinsoo; Han, Ki-Tek; Jeon, Dayeong; Lee, Bongsoo; Park, Byung Gi (Journal of the Korean Physical Society, 2012)
In this study, we developed an embedded infrared fiber-optic temperature sensor for thermometry in high temperature/pressure and water-chemistry environments by using two identical silver-halide optical fibers. The performance of the fabricated temperature sensor was assessed in an autoclave filled with an aqueous coolant solution containing boric acid and lithium hydroxide. We carried out real-time monitoring of the infrared radiation emitted from the signal and reference probes for various temperatures over a temperature range from 95 to 225 °C. In order to decide the temperature of the synthetic coolant solution, we measured the difference between the infrared radiation emitted from the two temperature-sensing probes. Thermometry with the proposed sensor is immune to any changes in the physical conditions and the emissivity of the heat source. From the experimental results, the embedded infrared fiber-optic temperature sensor can withstand, and normally operate in a high temperature/pressure test loop system corresponding to the coolant system used for nuclear power plant simulation. We expect that the proposed sensor can be developed to accurately monitor temperatures in harsh environments.